Práticas inovadoras de ensino: uso de brinquedos no ensino de algoritmos - Correia, Carlos Henrique; de Souza Domingues, Maria José Carvalho (Revista Gestão da Produção Operações e Sistemas, 2007)
The skills comprised in building algorithms and data structure are essential in computer programming. Nevertheless,the students present difficulties in understanding and coping with these abstract concepts. The body usein learning – especially with games and toys – enhances the learning process, thus increasing the understandingof abstract concepts by the students. The use of building toys such as “Lego” in the teaching of Algorithms andData Structures allowed for a better assimilation of fundamental programming concepts by the students, thusincreasing their interest and involvement in the discipline.Keywords: Teaching of algorithms; Innovative teaching practices; Learning styles.